2016
DOI: 10.1038/srep24047
|View full text |Cite
|
Sign up to set email alerts
|

Clg2p interacts with Clf and ClUrase to regulate appressorium formation, pathogenicity and conidial morphology in Curvularia lunata

Abstract: Ras is a small GTPase that regulates numerous processes in the cellular development and morphogenesis of many organisms. In this study, we identified and functionally characterized the Clg2p gene of Curvularia lunata, which is homologous with the Ras protein. The Clg2p deletion mutant (ΔClg2p) had altered appressorium formation and conidial morphology and produced fewer, smaller lesions compared with the wild-type strain. When a dominant Clg2p allele was introduced into the mutant, all of these defective pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Curvularia lunata is an important fungal pathogen that causes Curvularia leaf spot (CLS), which is one of the most widely distributed maize leaf diseases worldwide ( Gao et al, 2015a ; Liu et al, 2016 ). To uncover the pathogenicity mechanisms of CLS, most researches have focused on identifying virulence factors, such as melanin ( Gao et al, 2012 , 2015b ), and toxin ( Gao et al, 2014a ; Liu et al, 2009 ).…”
mentioning
confidence: 99%
“…Curvularia lunata is an important fungal pathogen that causes Curvularia leaf spot (CLS), which is one of the most widely distributed maize leaf diseases worldwide ( Gao et al, 2015a ; Liu et al, 2016 ). To uncover the pathogenicity mechanisms of CLS, most researches have focused on identifying virulence factors, such as melanin ( Gao et al, 2012 , 2015b ), and toxin ( Gao et al, 2014a ; Liu et al, 2009 ).…”
mentioning
confidence: 99%
“…A previous study demonstrated that Clg2P was involved in C. lunata conidial morphology and appressoria-related pathogenicity (Liu et al, 2016). The ClK1 disruption mutants of C. lunata produced fewer conidia and had lower infection rate on maize leaves (Gao et al, 2013).…”
Section: Discussionmentioning
confidence: 97%
“…A previous study demonstrated that Clg2P was involved in C . lunata conidial morphology and appressoria‐related pathogenicity (Liu et al ., 2016). The ClK1 disruption mutants of C .…”
Section: Discussionmentioning
confidence: 99%
“…It was found that Clg2p interacted with both Clf and ClUrase to regulate appressorium formation, conidial morphology and pathogenicity in C . lunata (Liu et al ., 2016).…”
Section: Introductionmentioning
confidence: 99%